Improving Coverage and Compliance in Mass Drug Administration for the Elimination of LF in Two 'Endgame' Districts in Indonesia Using Micronarrative Surveys. - Alison Krentel; Rita Damayanti; Christiana Rialine Titaley; Nugroho Suharno; Mark Bradley; Timothy Lynam (Public Library of Science (PLoS), 2016)
BACKGROUND:As the Global Programme to Eliminate Lymphatic Filariasis (LF) approaches its 2020 goal, an increasing number of districts will enter the endgame phase where drug coverage rates from mass drug administration (MDA) are used to assess whether MDA can be stopped. As reported, the gap between reported and actual drug coverage in some contexts has overestimated the true rates, thus causing premature administration of transmission assessment surveys (TAS) that detect ongoing LF transmission. In these cases, districts must continue with additional rounds of MDA. Two districts in Indonesia (Agam District, Depok City) fit this criteria-one had not met the pre-TAS criteria and the other, had not passed the TAS criteria. In both cases, the district health teams needed insight into their drug delivery programs in order to improve drug coverage in the subsequent MDA rounds. METHODOLOGY/PRINCIPAL FINDINGS:To inform the subsequent MDA round, a micronarrative survey tool was developed to capture community members' experience with MDA and the social realm where drug delivery and compliance occur. A baseline survey was implemented after the 2013 MDA in endemic communities in both districts using the EPI sampling criteria (n = 806). Compliance in the last MDA was associated with perceived importance of the LF drugs for health (p<0.001); perceived safety of the LF drugs (p<0.001) and knowing someone in the household has complied (p<0.001). Results indicated that specialized messages were needed to reach women and younger men. Both districts used these recommendations to implement changes to their MDA without additional financial support. An endline survey was performed after the 2014 MDA using the same sampling criteria (n = 811). Reported compliance in the last MDA improved in both districts from 57% to 77% (p<0.05). Those who reported having ever taken the LF drug rose from 79% to 90% (p<0.001) in both sites. CONCLUSIONS/SIGNIFICANCE:Micronarrative surveys were shown to be a valid and effective tool to detect operational issues within MDA programs. District health staff felt ownership of the results, implementing feasible changes to their programs that resulted in significant improvements to coverage and compliance in the subsequent MDA. This kind of implementation research using a micronarrative survey tool could benefit underperforming MDA programs as well as other disease control programs where a deeper understanding is needed to improve healthcare delivery.